The Influence of Tariff Changes, Taxation Socialization on Taxpayer Compliance Which Is Moderized by The Modernization of The Taxation System - Laksono, Untung Yuda; Taryanto, Taryanto; Sudraja, Enjat (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
The government has issued a tariff adjustment policy that applies to MSME players in an effort to increase the level of compliance. This research was also conducted to determine the effect of tax socialization on MSME taxpayer compliance which is moderated by the modernization of the tax system. The method used in this research is descriptive quantitative. The sample used is 99.5 (rounded 100) out of 189,600 Population of Micro, Small and Medium Enterprises in Pandeglang Regency, Banten. Data collection in this research used a questionnaire, while the hypothesis test used Moderated Regression Analysis (MRA) which was processed using SPSS 25 software. From this research, the results showed that changes in tariffs had a significant effect on MSME taxpayer compliance with a significance value (0.013 < 0.05). Tax socialization has a significant effect on MSME taxpayer compliance with a significance value (0.001 <0.05). Modernization of the taxation system moderates the effect of changes in tariffs on MSME taxpayer compliance with a significance value (0.06 <0.05). Modernization of the tax system moderates the effect of tax socialization on MSME taxpayer compliance with a significance value of (0.001 < 0.05). The findings in this study the variable of modernization of the tax system in this study is a moderating variable.